Turning the table on miRNAs - de la Mata, Manuel (2018)
Transcripts with highly complementary sequences can target microRNAs (miRNAs) for degradation, but the physiological relevance of target-directed miRNA degradation (TDMD) has remained unclear. Bitetti et al. now identify a conserved vertebrate RNA that induces TDMD in the cerebellum of zebrafish and mouse to promote wild-type animal behaviors.